BIOMATERIALS AS POROUS SCAFFOLDS FOR TISSUE ENGINEERING APPLICATIONS: A REVIEW - Zohora, Fatema Tuj; Anwarul Azim, Abu Yousuf Mohammad (European Scientific Journal, ESJ, 2014)
In tissue engineering, biomaterials play a critical role, act as a 3D template, provide mechanical support, and give artificial extracellular matrix environment (ECM) for neo-tissue formation. Only one type of biomaterials is not enough for both hard and soft tissue engineering. That’s why all types of biomaterials i.e. metals, ceramics, & polymers have their own importance in making tissue engineering scaffolds. This article presents a brief overview on all types of biomaterials (metals, ceramics, natural and synthetic polymers, composite materials, & hydrogels) that are being developed for soft or hard tissue engineering with their properties, limitations, current developments and future challenges in tissue engineering applications. This article also represents brief discussion on tissue engineering triad i.e. scaffolds, signal, & cells.